Concepções de professores do Ensino Fundamental I sobre a aprendizagem e o uso de tecnologia em sala de aula - Costa, Priscila Gabriela (2020)
The aim of this study is to investigate the conceptions of Elementary School teachers about learning in the Digital Age, taking into consideration the changes that occurred with the development of technology in our society. For this purpose, we investigated teachers’ perceptions about learning, advantages and limitations of the use of technology in the classroom and the teacher’s role in this context. As a theoretical framework, we used the learning theories of David Ausubel and Seymour Papert. For the production of data, we used semi-structured interviews carried out with teachers from the 1st to the 4th year of some Elementary Schools located in the state of São Paulo. The data were analyzed according to the Content Analysis methodology. It was found that the use of technologies in the classroom motivates the students and arouses their interest, which can impact on learning. On the other hand, it also allowed us to verify that teachers do not draw a clear distinction between teaching and learning; they do not use intentionally technology to facilitate cognitive learning; and that, sometimes, technological resources are implemented as strategies to diversion in the classroom or to reproduce what is done on paper. Nevertheless, they see technology as a facilitator in accessing information and as a motivating resource for students. Some limitations they presented are related to excessive information, superficial reading, addiction and lack of social skills of students due to the excessive use of certain technology resources. In order to improve the quality of education, initial and ongoing teacher education must ensure that teachers can use technology as a valuable tool for student learning